Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Kolam Renang Bengawan Solo Pangkalan Brandan) - Nasib Nasib (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This type of research is a causal research, useful for analyzing how a variable affects other variables, and also useful in experimental research in which the independent variables are treated in a controlled manner by the researchers to see the effects on the dependent variable directly. The result of simple regression analysis is Y = 4.764 + 0,198X1 + 0,096X2 + 0,425X3 + 0,268X4 + 0,602X5 + e which variable of physical evidence, reliability, responsiveness, assurance and empathy positive and significant influence to customer satisfaction at Bengawan Solo swimming pool . The test results (t) or partial test indicate that all the independent variables of physical evidence, reliability, responsiveness, assurance and empathy have a positive and significant effect on customer satisfaction. The result of determination test (R2) is 0804 (80,4%). So it can be said that 80.4% variation of bound variable that is physical evidence, reliability, responsiveness, assurance and empathy in the model can explain the satisfaction of visitors while the rest of 19.6% influenced by other variables outside the model.